Right from birth learning and intelligence - Rodmayer, Ron; Gibson, John; Hartman, Diane (New York: Insight Media, 2001)
This program focus on child development psychology
Executive producer, Rick Klein
Presenter: Karen Jones
Keywords: Child development; Infant; Infants -- Development